Serum Keratin 1 and TMAP in cardiac function prognosis of acute heart failure (AHF): Serum Keratin 1 and TMAP in the prognosis of AHF - She, Chengqun; Wu, Juan; Feng, Yaoguang; Long, Chaozhong; Tan, Zusong (Journal of Medical Biochemistry, 2026)
[Objective] To explore the relationships between serum TMAP (Tumor metastasis-associated peptide) and KRT1(Keratin 1) levels and the cardiac function classification and prognosis of patients with acute heart failure (AHF). [Methods] From January 2022 to January 2025, 428 patients with acute heart failure (AHF) admitted to this hospital composed the AHF group. Among them, 162 patients had a NYHA cardiac function classification of grade II, 166 patients had a grade III, and 100 patients had a grade IV. The control group consisted of 100 more healthy volunteers who had physical examinations at the same hospital during the same time period. After the AHF patients received relevant treatments according to the guidelines and were discharged, a 6-month follow-up was conducted. Patients with a poor prognosis were those who were readmitted due to heart failure or cardiac death; patients with a positive prognosis were those who were not. Each study participant’s serum levels of KRT1 and TMAP were determined using the enzyme-linked immunosorbent assay (ELISA). Patients with AHF were given baseline data. The relationship between the classification of cardiac function in AHF patients and serum TMAP and KRT1 levels was examined using Spearman correlation analysis. The factors determining a poor prognosis in individuals with AHF were examined using multivariate logistic regression analysis. The capacity of serum TMAP and KRT1 levels to predict a bad prognosis in AHF patients was examined using receiver operating characteristic (ROC) curves. Comparisons of the area under the curve (AUC) were conducted using the DeLong test. [Results] Serum TMAP levels were greater in the AHF group than in the control group (P < 0.05), and serum KRT1 levels were lower in the AHF group than in the control group (P < 0.05). The serum TMAP level increased with increasing cardiac function classification (F trend = 109.195, P trend < 0.001). Conversely, as heart function categorization increased, the serum KRT1 level dropped (F trend = 223.564, P trend < 0.001). According to Spearman correlation analysis, the cardiac function classification in AHF patients was positively connected with the serum TMAP level (r s = 0.711, P < 0.001) and inversely correlated with the serum KRT1 level (r s = -0.722, P < 0.001). TMAP, KRT1, and N-terminal pro-B-type natriuretic peptide (NT-pro BNP) levels, along with the NYHA cardiac function classification, varied statistically significantly (P < 0.05) between the groups with bad and favorable prognoses. Elevated NT-pro BNP levels, elevated TMAP levels, and NYHA cardiac function classification grade IV were found to be independent risk factors for a poor prognosis in AHF patients (P < 0.05), while elevated KRT1 levels were found to be an independent protective factor against a poor outcome in AHF patients (P < 0.05), according to multivariate logistic regression analysis. The areas under the curve (AUCs) for serum TMAP and KRT1 alone and jointly were 0.782, 0.792, and 0.880, respectively, for predicting a poor prognosis in AHF patients, according to ROC curve analysis. The AUC of the combination of the two was greater than that of the single prediction of serum TMAP and KRT1 (Z = 3.956, 3.642; P < 0.001). [Conclusion] Serum TMAP levels are elevated in patients with AHF, whereas KRT1 levels are decreased. Both of these factors are related to the patients’ cardiac function classification and prognosis. Combined serum TMAP and KRT1 levels have relatively high predictive efficacy for poor prognosis in patients with AHF.